The Integrative Role of Sulforaphane in Preventing Inflammation, Oxidative Stress and Fatigue: A Review of a Potential Protective Phytochemical - Ruheea Taskin Ruhee; Katsuhiko Suzuki (MDPI AG, 2020)
Cruciferous vegetables hold a myriad of bioactive molecules that are renowned for possessing unique medicinal benefits. Sulforaphane (SFN) is one of the potential nutraceuticals contained within cruciferous vegetables that is useful for improving health and diseased conditions. The objective of this review is to discuss the mechanistic role for SFN in preventing oxidative stress, fatigue, and inflammation. Direct and indirect research evidence is reported to identify the nontoxic dose of SFN for human trials, and effectiveness of SFN to attenuate inflammation and/or oxidative stress. SFN treatment modulates redox balance via activating redox regulator nuclear factor E2 factor-related factor (Nrf2). SFN may play a crucial role in altering the Keap1/Nrf2/ARE pathway (an intricate response to many stimuli or stress), which induces Nrf2 target gene activation to reduce oxidative stress. In addition, SFN reduces inflammation by suppressing centrally involved inflammatory regulator nuclear factor-kappa B (NF-κB), which in turn downregulates the expression of proinflammatory cytokines and mediators. Exercise may induce a significant range of fatigue, inflammation, oxidative stress, and/or organ damage due to producing excessive reactive oxygen species (ROS) and inflammatory cytokines. SFN may play an effective role in preventing such damage via inducing phase 2 enzymes, activating the Nrf2/ARE signaling pathway or suppressing nuclear translocation of NF-κB. In this review, we summarize the integrative role of SFN in preventing fatigue, inflammation, and oxidative stress, and briefly introduce the history of cruciferous vegetables and the bioavailability and pharmacokinetics of SFN reported in previous research. To date, very limited research has been conducted on SFN's effectiveness in improving exercise endurance or performance. Therefore, more research needs to be carried out to determine the effectiveness of SFN in the field of exercise and lifestyle factors.